Cycle Threshold (CT) and Neutrophil-To-Lymphocyte (NLR) Values As Predictors of Clinical Symptoms in Pediatric Covid-19 Cases: A Systematic Literature Review - Sabar Hutabarat; Wahyu Indah Dewi Aurora (PT Inovasi Pratama Internasional, 2024)
Background: The COVID-19 epidemic has impacted persons across all age demographics, including children. An opposing viewpoint is that despite the extensive discussion surrounding the neutrophil-to-lymphocyte ratio as a potential indicator of clinical symptoms in pediatric COVID-19 cases. This systematic literature review aims to explores the correlation between CT readings, neutrophil-to-lymphocyte ratio, and clinical symptoms in pediatric cases with COVID-19. Method: This systematic review examined the existing research on Cycle Treshold (CT) and Neutrophil-To-Lymphocyte Ratio (NLR) values as indicators of the clinical progression in children with COVID-19. An extensive search of databases Scopus revealed studies that satisfied our inclusion criteria. They utilized CT valuess and the neutrophil-to-lymphocyte ratio as indicators for predicting clinical symptoms. The inclusion criteria for this study were specifically centered around juvenile patients with COVID-19 from scopus databased. The chosen studies underwent a thorough evaluation to determine their quality and relevance. Various nations, including Korea, China, Italy, the United States, Egypt, South Africa, India, Japan, Brazil, and others. Result: The papers included in the analysis demonstrate a noteworthy correlation between CT readings and clinical symptoms in children with COVID-19 Pediatric COVID-19 cases with elevated CT values demonstrated a greater propensity for severe clinical manifestations, including respiratory distress and pneumonia. Upon reviewing the available research, it is evident that hematological parameters, specifically the neutrophil-to-lymphocyte ratio, significantly impact forecasting the severity and clinical prognosis of juvenile COVID-19 cases. Conclusion: The neutrophil-to-lymphocyte ratio and CT values were identified as dependable indicators of illness severity in pediatric patients. The results emphasize the significance of hematologic measures, specifically the neutrophil-to-lymphocyte ratio, as helpful markers for evaluating the clinical symptoms and outcomes of juvenile COVID-19 patients.